Chlorophyll concentration and grain production in Avena sativa L. with two doses of nitrogen fertilizer - Blanco Alves, Carlos Nicolás; Beltramelli Gula, Marcos Osvaldo (Acta Iguazu, 2021)
The productive potential of a crop can be known by indirect measurements of the chlorophyll content. The objective of this research was to evaluate the chlorophyll content and the grain production of the oat crop, in direct sowing, with two doses of rainfed nitrogen and a control without added fertilizer. The experimental design used was randomized blocks with 12 repetitions for grain yield. The size of the plot was 25 m-2. The cultivar used was Estanzuela 1095a and 2 different doses of N were used (25 and 50 kg ha-1). The chlorophyll content in the last fully developed leaf and the grain yield were measured. The results indicated that there were no significant differences in the chlorophyll a and b index as well as there were no differences in the total chlorophyll index and in the ratio of the chlorophyll a / b index. The grain yield and the weight of one thousand grains did not show significant differences.